In Vivo and In Vitro Analyses of Novel Peptidomimetic Disruptors for the Serotonin 5-HT2C Receptor Interaction With Phosphatase and Tensin Homolog - Soto, Claudia A.; Du, Huang-Chi; Fox, Robert G.; Yang, Taegyun; Hooson, James; Anastasio, Noelle C.; Gilbertson, Scott R.; Cunningham, Kathryn A. (Frontiers in Pharmacology, 2019)
Hypofunction of the serotonin (5-HT) 5-HT2C receptor (5-HT2CR) has been implicated in a variety of disorders including substance use disorders. As such, approaches to enhance 5-HT2CR signaling display therapeutic potential. In the present study, we show that disruption of the 5-HT2CR interaction with the protein phosphatase and tensin homolog (PTEN) via peptidomimetics enhances 5-HT2CR-mediating signaling in vitro and potentiates selective 5-HT2CR agonists in behavioral rodent models. Overall, the present study provides further evidence that 5-HT2CR activity can be modulated through an allosteric protein–protein interaction. This work provides the groundwork for the continued exploration of protein–protein interactions that can allosterically modulate this critical receptor and other important G protein-coupled receptors (GPCRs) for new therapeutic development through mechanisms that may display clinical utility.